Fast and Efficient Monitoring of Diclofenac Dissolution Profile by CE - Monzón, Celina María (2014)
Capillary electrophoresis (CE) was used to follow Diclofenac tablet dissolution, in very short times and allowing dissolution testing without volume replacement. By using Student´s t test and F-test, this CE method was compared with HPLC. Statistical data show that there are no significant differences among them. The drug release kinetic of diclofenac tablets was described by various mathematical models and equations. Model-Independent Methods: t50% = 10.34 min; t80% = 20 min; DE% = 79.41% and MDT = 10.85 min, show that diclofenac tablet dissolution rate is very high, having 80% drug dissolution within 20 minutes. Model-Dependent Methods. The kinetics models used were: zero order, first order, Hixson?Crowell cube root law, Higuchi model, and Weibull model. Criteria used to choose the best model was by comparisson of r2 and AIC (Akaike Information Criteria). The model that best adjusts diclofenac tablet dissolution profile was the Hixson-Crowell cube root model.